EFFECTIVENESS OF WORDWALL LEARNING MEDIA ON INDONESIAN LANGUAGE LEARNING OUTCOMES OF GRADE III STUDENTS OF MI MA'ARIF KUMPULREJO 02 SALATIGA - Aminullah, Muhammad Hikam; Rahman, Ithafur (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to examine the effectiveness of Wordwall, a digital game-based learning platform, in improving the ability of third-grade students to construct simple sentences in Indonesian language learning. The research was motivated by observed difficulties among students in mastering sentence structure, often exacerbated by the lack of engaging and interactive learning media in traditional classrooms. Using a quasi-experimental design with pretest-posttest and control groups, data were collected from 47 students at MI Ma'arif Kumpulrejo 02 Salatiga. The experimental group received instruction using Wordwall, while the control group followed conventional teaching methods. Data collection instruments included multiple-choice tests that underwent rigorous validation procedures to ensure reliability, difficulty level, and discrimination power. Findings revealed that the experimental group significantly outperformed the control group, as demonstrated by higher posttest scores, a significant result in the independent sample t-test, and an N-Gain score of 73.08%, categorized as effective. These results suggest that Wordwall fosters improved engagement, comprehension, and performance in language instruction. The study supports Bruner's constructivist theory and Skinner's behaviorist learning principles by emphasizing active participation and reinforcement. Furthermore, the results are consistent with previous studies that highlight the educational potential of game-based media in enhancing student achievement. The study contributes to the growing body of research on digital learning in elementary education and underscores the need for integrating interactive technology in language instruction. Future research is encouraged to explore long-term effects, application in other subjects, and comparisons with other digital platforms to further expand the understanding of educational technology's role in improving learning outcomes. Keywords: Wordwall, Indonesian Language Learning, Learning Outcomes, Elementary Education, Educational Technology